Descriptive Study of Parenting in Pedophilia Offenders - Iswanto, Bambang; Ningsih, Yuninda Tria (Universitas Ibn Khaldun Bogor, 2025)
Sexual violence is a phenomenon that occurs around the world and in Indonesia. Data shows that victims of sexual crimes are dominated by the age group 13-17 years, while the perpetrators are dominated by the age group 25-44 years. In this case, adults who commit sexual crimes against children are called pedophiles. This study aims to determine the type of parenting that is most highly applied to pedophiles. This study uses descriptive quantitative methods. The scale used in this study is the Parenting Styles and Dimensions Questionnaire (PSDQ) (Robinson et al., 1995) which was later translated and validated by Fahiroh, Tairas, and Retnowati (2019). The research was conducted on inmates of correctional institutions with child protection cases. The results showed that the subjects in this study received permissive and authoritarian parenting in the high category, while democratic parenting was in the low category. It can be concluded that permissive and authoritarian parenting are the types of parenting most often applied to pedophiles.